TINJAUAN HASIL INSEMINASI BUATAN SAPI BALI DI DESA PUKDALE KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Jefrysandi Dapasesi; Tarsisius C. Tophianong; Cynthia D Gaina (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2020)
Bali Cattle is one of regional economic support for East Nusa Tenggara (NTT). Bali Cattle has a particularly important role for the that is as the supplier of animal protein, a source of income, savings and field works. Bali cattle most popular in NTT particular in Village Pukdale East kupang sub- District Kupang Regency. The purpose of this study is to find Service per conception (S/C), Pregnancy Rate, Days Open (DO) and Calving Interval (CI) of Bali cattle be inseminated in village Pukdale East Kupang Sub- District Kupang Regency. The number of cattles used in this study were 30 cows. This research used female Bali cattle at least two times calve, age 4-7 years, Body Condition Score (BCS) 3-2 from standard 5-1 and has not disorder reproduction .The research results show that average score Service per conception (S/C) 2,33, Pregnancy Rate 60 %, Days Open 102,3 days and Calving Intervals (CI) 13,019 months. The results of the study showing that the Pregnancy Rate, Days Open (DO) and Calving Intervals (CI) is in the range of normal while value Service per conception (S/C) unwell so it needs of an improvement on the implementation of the program artificial insemination in the village pukdale covering the ability farmers in detecting estrus and the availability of nitrogen (N2) liquid